PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT JOVENINDO INTI SOLUSI JAKARTA - Deni Nursanjaya; Suwanto (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the Influence of Leadership and Work Discipline on Employee Performance at PT Jovenindo Inti Solusi Jakarta, both partially and simultaneously. This research method uses a quantitative method with a sample of 78 respondents, data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression test, multiple correlation coefficient test, determination coefficient analysis test, t test and F test. Partially, leadership on employee performance obtained a Sig value <0.05 (0.001 <0.05) and a calculated t value> t table (3.412> 1.99). These results mean that there is a significant influence of leadership on employee performance and as a basis for the decision of the hypothesis taken, namely accepting Ha and rejecting Ho. The partial significance test of work discipline on employee performance obtained a Sig value <0.05 (0.000 <0.05) and a calculated t value> t table (5.298> 1.99). These results mean that there is a significant influence of work discipline on employee performance and as a basis for the decision of the hypothesis taken, namely accepting Ha and rejecting Ho. The simultaneous significance test of leadership and work discipline on performance obtained a calculated F value> F table (34.969> 3.12) and a sig value (0.000 <0.05). These results mean that there is a significant influence of leadership and work discipline on employee performance and as a basis for the decision of the hypothesis taken, namely accepting Ha and rejecting Ho.